2018
DOI: 10.22219/ijota.v1i1.6082
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Strychnos ligustrina Bl. Extract as Feed Supplementation to Increase Immune System of Nile Tilapia (Oreochromis niloticus) wich againts Streptococcus agalactiae

Abstract: One of the problems of intensive cultivation of tilapia is the attack of Streptococcosis disease caused by Streptococcus agalactiae bacteria. To prevent it is necessary to prevent the use of natural antibiotics that is Strychnine bush extract. The method used in this research is the experimental method using Completely Randomized Design (RAL), then the data is analyzed by using ANAVA. In this research, there were five treatments with various dosages, namely treatment (K: 0%), (A: 5%), (B: 10%), (C: 15%) and (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…The decline was possibly because fish stressed due to injections so that their appetite decreased. Appetite of fish infected by bacteria decreased (Zubaidah et al, 2019). Sieira et al (2018) said that stress on fish could affect appetite, which had an impact on decreasing of feed consumption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The decline was possibly because fish stressed due to injections so that their appetite decreased. Appetite of fish infected by bacteria decreased (Zubaidah et al, 2019). Sieira et al (2018) said that stress on fish could affect appetite, which had an impact on decreasing of feed consumption.…”
Section: Resultsmentioning
confidence: 99%
“…The function of the thyroid hormone is to increase the levels of oxygen that will be used by cells. Oxygen in the body of the fish plays a role in the process of metabolism to produce energy and this energy is used to produce leukocyte cells in large quantities to produce antibodies (Zubaidah et al, 2019). Respiratory burst activity is directly proportional to phagocytic activity (Rawling et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…All doses (low, medium, and high doses) induced mortality in mice but had a non-dose-dependent increase. Previous research reported that methanol extract of S. ligustrina had a toxic effect on Nile tilapia (Oreochromis niloticus), such as decreasing HCT and leucocyte levels (Zubaidah et al, 2018). The high mortality was shown at the high doses in male and female groups, while the lowest mortality was in control groups (Table 1).…”
Section: Discussionmentioning
confidence: 86%
“…Hematological analysis was performed using a hematology analyzer (Mindray BC-2800vet) to evaluate erythrocyte (RBC), hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular Hb (MCH), MCH concentration (MCHC), red-cell distribution width (RDW), platelet (PLT), mean platelet volume (MPV), platelet distribution width (PDW), procalcitonin (PCT), leukocyte (WBC), lymphocyte, monocyte, and granulocyte (Zhang et al, 2021). Biochemistry analysis was performed using a clinical chemistry analyzer (SPOTCHEM™ EZ SP-4430) with the following parameters: alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), total protein (TP), total cholesterol total, glucose, urea (BUN), and creatinine (Lee et al, 2021).…”
Section: Hematological and Biochemistry Studymentioning
confidence: 99%
“…Supplementation with a natural antibiotic called snogga wood ( Strychnos ligustrina Bl. ) at a dose of 10% per feed elevated phagocytosis and leukocyte count and showed activity against Streptococcus agalactiae ; however, it did not alter hematocrit and leukocrit levels in Nile tilapia at any dose examined [ 88 ]. Pawpaw or papaya ( Carica papaya ) is a tropical plant from Central America and southern Mexico that contains unlike groups of bioactive agents, including saponins, flavonoids, carotenoids, and proteolytic enzymes.…”
Section: The Effect Of Herbal Extracts and Plant Components On Immune-related Genes In Fish Speciesmentioning
confidence: 99%